For public or profession?--The new GMC performance procedures. Issue 6861 (31st October 1992) - Stacey, M.
Abstract : The upheaval in the General Medical Council two decades ago came from doctors not the consumers the council was set up to protect. Since then there have been repeated calls for doctors to improve their self regulation by amending the disciplinary procedures. Private member's bills have failed and the GMC has now proposed performance procedures to deal with doctors who exhibit a "pattern of poor performance." After months of wide consultation in and outside the medical profession the GMC will decide next week whether to endorse the procedures, which unlike the conduct hearings will be inquiries by peers. Professor Margaret Stacey suggests that the procedures lack clarity, smacking of that "trust me" principle whose subtext is "but I'm not telling you what I'm up to."